249 Is Our Diabetic Control Too Tight? An Audit of Management of Type II Diabetes in a Long Term Care Setting. (16th September 2019) - MacMahon, Clare; O'Gorman, Millie; Martin, John; Doyle, Marie; O'Donoghue, Alice; O'Donnell, Desmond; O'Mahoney, Anne; Henin, Maged; John, Cooke; Pope, George; Mulcahy, Riona
Abstract: Background: Recent guidelines on diabetes management recommend individualisation of management particularly in those with frailty or significant co-morbidities. The aim of our audit was to assess diabetic control of residents in a long term care setting. Studies have shown that intensive control in an older population increases the risk of hypoglycaemia and does not necessarily improve clinical outcomes. There is also evidence that increased pill burden and hypoglycaemic events negatively affect quality of life among older people. Methods: 176 nursing home residents were assessed. Detailed chart review was carried out on the 47 residents with a diagnosis of type 2 diabetes. Information collated included age, sex, diabetes type, frequency of blood sugar monitoring, weight, BMI, Clinical Frailty Scale, allocation of diabetic diet and treatments including insulin and oral hypoglycaemic agents. Diabetic control was assessed by HbA1c. Evidence of hypoglycaemia in the preceding four weeks was documented. Results: Of 47 patients (33 female), average age was 79.8 years and median BMI was 25. 41/47 residents had a Clinical Frailty Score of 6 or greater. The median HbA1c overall was 44mmol/l (range was 29-116mmol/l). All patients were on a diabetic diet. 23/47 residents on oral hypoglycaemic agents and the median HbA1c of this group was 51mmol/l. 6/47 were on insulin. Sugars were checked weekly (daily in those on insulin) and HbA1c was checked in the previous 6 months in 36/47.There was 1 recorded hypoglycaemic episode. Conclusion: Our data showed that long stay residents continue to have tight diabetic control despite low BMI, evidence of frailty, significant co morbidities and dependency. HbA1c can also decrease due to renal disease, weight loss and poor oral intake. In line with recent guidelines our data shows there is scope to rationalise diabetic treatment regimens with reduction in polypharmacy and improvement in quality of life.